2014
DOI: 10.1136/bcr-2013-200182
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary molar distalization with first class appliance

Abstract: SUMMARYNon-extraction treatment has gained popularity for corrections of mild-to-moderate class II malocclusion over the past few decades. The distalization of maxillary molars is of significant value for treatment of cases with minimal arch discrepancy and mild class II molar relation associated with a normal mandibular arch and acceptable profile. This paper describes our experience with a 16-year-old female patient who reported with irregularly placed upper front teeth and unpleasant smile. The patient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This is in agreement with many studies and indicated that there is variations in canine and premolar tooth width between races and ethnic groups. (5,31) ISSN: 1110-435X ONLINE ISSN: 281-5258 Regarding females, statistically significant differences existed between the measured and predicted values using Moyer prediction tables at 35 th , 50 th , 75 th percentile, except for the 50 th percentile in the mandibular arches. This results is similar to conclusions of other studies that indicated inacuracy of moyer prediction tables for females.…”
Section: Discussionmentioning
confidence: 94%
“…This is in agreement with many studies and indicated that there is variations in canine and premolar tooth width between races and ethnic groups. (5,31) ISSN: 1110-435X ONLINE ISSN: 281-5258 Regarding females, statistically significant differences existed between the measured and predicted values using Moyer prediction tables at 35 th , 50 th , 75 th percentile, except for the 50 th percentile in the mandibular arches. This results is similar to conclusions of other studies that indicated inacuracy of moyer prediction tables for females.…”
Section: Discussionmentioning
confidence: 94%